Mexican Deregulation: Smart Tape on Red Tape - José Salas, Fernando (Washington, DC: World Bank, 2012)
Since 1989, UDE/COFEMER, the Mexican deregulation/regulatory agency, has persuasively tapped Executive support and used its authority to propose effective deregulation and better regulation. This paper explains how this commission came about and operated, first to focus on federal red tape reduction and then to institutionalize a system of regulatory management at the federal level.